Make money easy : create financial freedom and live a richer life - Howes, Lewis (Hay House, Incorporated, 2025)
"Are you tired of living paycheck to paycheck? Do you feel trapped by all your expenses every month? Do you wonder how some people enjoy financial peace and freedom while others seem stuck? Your relationship with money begins with having the right mindset. Until you learn how to shift your thoughts, feelings, and behaviors around money, you'll keep doing what you've always done. And get the same results. Leveraging insight gleaned from the many financial experts on the School of Greatness show, the latest research around the psychology of money, and his own journey to success, Lewis Howes offers the practical advice and mindset reframing to make the peace and fulfillment you desire a day-to-day reality."--Amazon.com.